Assessing economic investment required to scale up bariatric surgery capacity in England: a health economic modelling analysis - Richard Welbourn; Yuxin Li; Ines Guerra; Dimitri J Pournaras; Abd Tahrani; James Baker-Knight; Kamal Mahawar; Yuvraj Sharma (BMJ Open, 2024)
Objectives To quantify the economic investment required to increase bariatric surgery (BaS) capacity in National Health Service (NHS) England considering the growing obesity prevalence and low provision of BaS in England despite its high clinical effectiveness.Design Data were included for the patients with obesity who were eligible for BaS. We used a decision-tree approach including four distinct steps of the patient pathway to capture all associated resource use. We estimated total costs according to the current capacity (current scenario) and three BaS scaling up strategies over a time horizon of 20 years (projected scenario): maximising NHS capacity (strategy 1), maximising NHS and private sector capacity (strategy 2) and adding infrastructure to NHS capacity to cover the entire prevalent and incident obesity populations (strategy 3).Setting BaS centres based in NHS and private sector hospitals in England.Main outcome measures Number of BaS procedures (including revision surgery), cost (GBP) and resource utilisation over 20 years.Results At current capacity, the number of BaS procedures and the total cost over 20 years were estimated to be 140 220 and £1.4 billion, respectively. For strategy 1, these values were projected to increase to 157 760 and £1.7 billion, respectively. For strategy 2, the values were projected to increase to 232 760 and £2.5 billion, respectively. Strategy 3 showed the highest increase to 564 784 and £6.4 billion, respectively, with an additional 4081 personnel and 49 facilities required over 20 years.Conclusions The expansion of BaS capacity in England beyond a small proportion of the eligible population will likely be challenging given the significant upfront economic investment and additional requirement of personnel and infrastructure.